2017
DOI: 10.1007/s12020-017-1227-3
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations among the adipocytokines leptin and adiponectin, oxidative stress and aseptic inflammation markers in pre- and early-pubertal normal-weight and obese boys

Abstract: In all subjects, leptin and adiponectin predict negatively and positively anti-oxidation, respectively, while high sensitivity IL-6 predicts positively and negatively pro- and anti-oxidation, respectively. High-sensitivity C-reactive protein is increased and negatively associated with anti-oxidation in pre-pubertal obese boys, suggesting that childhood obesity is associated with aseptic inflammation and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 53 publications
2
40
0
2
Order By: Relevance
“…The mechanisms underlying the development of obesity and its associated comorbidities include hypertrophy and hyperplasia of primarily visceral adipocytes, adipose tissue inflammation, impaired extracellular matrix remodeling, and fibrosis, together with altered secretion of adipokines [11,57,58]. Chronically stressful conditions cause hypertrophy and hyperplasia of the adipocytes, alter the secretion of adipokines, and cause attraction and activation of stromal fat immune cells [59][60][61].…”
Section: Muscle Mass: Myosteatosis and Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the development of obesity and its associated comorbidities include hypertrophy and hyperplasia of primarily visceral adipocytes, adipose tissue inflammation, impaired extracellular matrix remodeling, and fibrosis, together with altered secretion of adipokines [11,57,58]. Chronically stressful conditions cause hypertrophy and hyperplasia of the adipocytes, alter the secretion of adipokines, and cause attraction and activation of stromal fat immune cells [59][60][61].…”
Section: Muscle Mass: Myosteatosis and Sarcopeniamentioning
confidence: 99%
“…It is caused by an imbalance between the energy input of the diet and the body's energy demands [9][10][11]. Fat accumulation in various tissues has been implicated in many metabolic disorders, such as non-alcoholic fatty liver disease (NAFLD) or hepatosteatosis [12] and myosteatosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown decreased levels of adiponectin in individuals with obesity [47, 48]. In pre-pubertal boys, there is a reported increase and negative association with anti-oxidation, suggesting a link between aseptic inflammation and oxidative stress and childhood obesity [49]. It has also been shown that parent stressors impact childhood obesity and African American and Hispanic children raised in single-parent households and children from low-income families were at major risk of partaking in activities, such as fast-food consumption at rates that were correlated with parent stressors [34].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the presence of low‐grade chronic inflammation and insulin resistance in young people, information on the inflammatory response to an acute bout of exercise in adolescents is limited. Previous studies examining the release of inflammatory mediators, IL‐6, and TNF‐α in response to an acute bout of endurance exercise have reported increases, decreases, or no changes . However, young people do not typically participate in endurance exercise, with intermittent activity being both enjoyable (important for long‐term adherence) and replicative of their physical activity patterns .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining the release of inflammatory mediators, IL-6, and TNF-α in response to an acute bout of endurance exercise have reported increases, 9,10 decreases, 11 or no changes. 12,13 However, young people do not typically participate in endurance exercise, with intermittent activity being both enjoyable (important for long-term adherence) 14 and replicative of their physical activity patterns. 15 Eccentric exercise is an alternative mode of physical activity that elicits an increase in the release of pro-inflammatory cytokines (IL-6 and IL-1β) in response to the muscle damage incurred.…”
Section: Introductionmentioning
confidence: 99%